Pathogens involved in fatal cases of diarrhea in young alpacas in the central highlands of Peru - Lucas L., Juan R. (2016)
The presence of enteric pathogens was assessed in 60 young alpacas (1 to 2.5 months old) raised in Pasco and Junin, Peru that died due to diarrhea. Stool samples were collected to determine the frequency of Escherichia coli and Salmonella sp by conventional microbiology, gastrointestinal parasites by the sedimentation and flotation techniques, and Cryptosporidium sp by the modified Ziehl Neelsen technique. Besides, the presence of viral antigens using an immunochromatography commercial kit. The results showed the presence of E. coli (80%), coronavirus (53.3%), Eimeria sp (43.3%), Nematodirus sp (40%), rotavirus (36.6%), Criptosporidium sp (20%) and Salmonella sp (18.3%). Moreover, it was determined that 38.3% of the animals presented the three types of pathogens, while 23.3% had association of bacteria and parasites, and 11.7% showed association of virus and bacteria.